Actividad antiinflamatoria in vitro del extracto etanólico e hidroetanólico de hojas y tallo de Senna quinquangulata - Uraco Mafaldo, Anthony Alejandro (Universidad Nacional de la Amazonía Peruana, 2025)
Senna quinquangulata is a plant preserved in the Loreto region, known for its extensive therapeutic properties in traditional medicine, including promising anti-inflammatory effects. Objective: To determine the anti-inflammatory activity of the ethanolic and hydroethanolic extracts of S. quinquangulata leaves and stems on plasma erythrocytes. Methodology: the leaves and stems were collected and used for the preparation of the alcoholic and hydroalcoholic extracts. The anti-inflammatory activity of these extracts was evaluated at concentrations of 10, 100, and 1000 µg/ml on plasma erythrocytes. Results: none of the evaluated concentrations of S. quinquangulata showed an inhibition rate greater than 50%, resulting in an IC50 > 1000 µg/mL. Conclusion: the tested extracts did not show anti inflammatory activity at the evaluated concentrations.

Senna quinquangulata es una planta conservada en la región de Loreto, conocida por sus amplias propiedades terapéuticas en la medicina tradicional, incluyendo prometedores efectos antiinflamatorios. Objetivo: Determinar la actividad antiinflamatoria del extracto etanólico e hidroetanólico de hojas y tallo de S. quinquangulata sobre eritrocitos plasmáticos. Metodología: las hojas y tallos fueron recolectados y utilizados para la preparación de los extractos alcohólico e hidroalcohólico. Se evaluó la actividad antiinflamatoria de estos extractos a concentraciones de 10, 100 y 1000 µg/ml sobre eritrocitos plasmáticos. Resultados: Ninguna de las concentraciones evaluadas de S. quinquangulata mostró una tasa de inhibición superior al 50%, obteniéndose así una IC50 > 1000 µg/mL. Conclusión: los extractos probados no mostraron actividad antiinflamatoria en las concentraciones evaluadas.
Keywords: Antiinflamatorios; Invitro; Extractos vegetales; Etáno; Extractos de hoja; Tallo; Senna quiquangulata; https://purl.org/pe-repo/ocde/ford#3.01.05; https://purl.org/pe-repo/ocde/ford#1.06.03